2018
DOI: 10.14444/5013
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal Lumbar Interbody Fusion With Viable Allograft: 75 Consecutive Cases at 12-Month Follow-up

Abstract: Background: When conservative treatments fail to alleviate the discomfort of abnormal motion, spinal fusion has been shown to provide symptomatic treatment for spinal instability, stenosis, spondylolisthesis, and symptomatic degenerative disc disease. The trend and rates of fusion over the past few years have been dramatic in the United States. Accompanying that higher incidence has been the shifting from traditional open surgery to minimally invasive techniques to reduce scar tissue formation, extent of muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In this study, we showed that a cell-seeded bone biomaterial is capable of consistently and successfully augmenting the mandibular bone, while presenting histological features of healthy living bone. Bone biomaterials have been safely used in the field of Orthopaedics surgery in the past 40 years 28 , and the new generation of viable bone biomaterial we tested in this study is currently being used for applications such as spine fusion with great success 26 . In addition, the remodeling of this cell-seeded bone biomaterial was more rapid and led to a larger bone formation compared to the acellular biomaterial used as a control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that a cell-seeded bone biomaterial is capable of consistently and successfully augmenting the mandibular bone, while presenting histological features of healthy living bone. Bone biomaterials have been safely used in the field of Orthopaedics surgery in the past 40 years 28 , and the new generation of viable bone biomaterial we tested in this study is currently being used for applications such as spine fusion with great success 26 . In addition, the remodeling of this cell-seeded bone biomaterial was more rapid and led to a larger bone formation compared to the acellular biomaterial used as a control.…”
Section: Discussionmentioning
confidence: 99%
“…The attempts of improving bone grafts using MSCs have shown good preliminary outcomes evidenced by clear differences between the enriched grafts and the non-cellularized grafts 2325 . Our group developed a cellularized bone substitute material which is currently available on the US market for spine fusion applications (ViaGraft ® , Vivex Biomedical, Miami, FL) 26 . This material is made of cadaveric human bone microparticles (30% cortical bone, 30% cancellous bone and 40% fully demineralized cortical bone) ranging from 100–300 microns in size and seeded with MSCs (see supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical challenges concomitant to tissue loss have benefitted from viable allograft in surgical fusions [43]. Moreover, with low complications, high regenerative potential, and economic value in reduced time to healing, higher rate of fusion, and shorter windows of recovery, advances in cryoprotectant technology will continue to improve.…”
Section: Resultsmentioning
confidence: 99%
“…Following the MIS-TLIF procedure, improvement in the interbody fusion rate minimizes hospitalization time, efficacy, and safety. Fusion is also impacted by bone materials (autograft/allograft or synthetic), cage size [ 32 ], osteoinductive molecules, viable cells, and regenerative materials [ 33 ]. On the contrary, meta-analysis has also reported that irrespective of the graft material, the fusion rate in MIS-TLIF is very high [ 34 ].…”
Section: Mis–tlif: the Surgical Proceduresmentioning
confidence: 99%
“…Autografts derived from iliac crest are rich in live cells, osteoinductive growth factors, and channels necessary for vascularization, which could promote effective lumbar fusion [ 95 ]. A retrospective study with 75 consecutive cases showed that iliac crest bone graft (ICBG) could effectively aid in achieving a higher rate of spinal fusion without any major perioperative or latent complications and transfusion [ 33 ]. Furthermore, no significant difference in postoperative pain/disability and blood loss was found between BMP-2 and ICBG-treated patients.…”
Section: Currently Employed Surgical Materials For Bone Grafting Amentioning
confidence: 99%